2013
DOI: 10.1371/journal.pone.0053705
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus and Pseudomonas aeruginosa Express and Secrete Human Surfactant Proteins

Abstract: Surfactant proteins (SP), originally known from human lung surfactant, are essential to proper respiratory function in that they lower the surface tension of the alveoli. They are also important components of the innate immune system. The functional significance of these proteins is currently reflected by a very large and growing number of publications. The objective goal of this study was to elucidate whether Staphylococcus aureus and Pseudomonas aeruginosa is able to express surfactant proteins. 10 different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…6,9,10 Along with the lung, glandular tissues are one of the most studied in this field. 17,20,28 We provide the first investigation on SPs in infantile labial glands and broaden the spectrum of occurrence.…”
Section: Discussionmentioning
confidence: 98%
“…6,9,10 Along with the lung, glandular tissues are one of the most studied in this field. 17,20,28 We provide the first investigation on SPs in infantile labial glands and broaden the spectrum of occurrence.…”
Section: Discussionmentioning
confidence: 98%
“…In 2013, Bräuer and colleagues made the first known determination of expression of all four SP's by bacteria (Brauer et al, 2013) in the bacterial strains Staphylococcus aureus and Pseudomonas aeruginosa . For all four SP's, genomic DNA was identified by PCR, mRNA transcripts identified by RT-PCR, protein expression was detected by western blotting and quantified by ELISA.…”
Section: Expression Of Surfactant Proteins In Bacteriamentioning
confidence: 99%
“…Surfactant proteins are an important part of the human immune system for fighting bacterial pathogens. It has now shown that the surfactant proteins also exist in pathogenic bacteria (Bräuer et al, 2013). Researchers have now shown these proteins to exist in two pathogenic types of bacteria, staphylococcus aureus and pseudomonas aeruginosa, which are both germs that can cause severe infections of the lungs and other organs.…”
Section: Pulmonary Surfactantmentioning
confidence: 99%